Hypothalamic superoxide dismutase, xanthine oxidase, nitric oxide, and malondialdehyde in rats fed with fish ?-3 fatty acids - Songur, A; Sarsilmaz, M; Sogut, S; Ozyurt, B; Ozyurt, H; Zararsiz, I; Turkoglu, AO (Pergamon-Elsevier Science Ltd, 2004)
Phosphohpids located in the cellular membrane play a critical role in the fluid-mosaic model of membrane structure and membrane function. Evidence is mounting for the role of abnormal phospholipid metabolism in some neuropsychiatric disorders including schizophrenia. As an important essential fatty acid (EFA), omega-3 (omega-3) fatty acid series are found in large amounts in fish oil. The aim of this experimental study was to assess the changes of some of the oxidant and antioxidant parameters in the hypothalamus of rats fed with omega-3 EFA diet (0.4 g/kg/day) for 30 days. Eight control rats and nine rats fed with omega-3 were decapitated under ether anesthesia, and hypothalamus was removed immediately. Malondialdehyde (NIDA) and nitric oxide (NO) levels as well as superoxide dismutase (SOD) and xanthine oxidase (XO) enzyme activities in the hypothalamus were measured. SOD activity was significantly decreased in omega-3 EFA treated group compared to control group (p < 0.014). Tissue NIDA and NO levels were also decreased in omega-3 EFA treated group compared to control rats (p < 0.0001). Xanthine oxidase activity was found to be increased in w-3 EFA treated rats when compared to the control group (p < 0.0001). Taken together, this preliminary animal study provides strong support for a therapeutic effect of omega-3 EFA in some neuropsychiatric disorders in which reactive oxygen species (ROS) are recently accused to be an important physiopathogenetic factor. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: hypothalamus; malondialdehyde; nitric oxide; omega-3 essential fatty acids; superoxide distrimase; xanthine oxidase